Age-specific comorbidity risks in osteoarthritis: implications for healthy aging across diverse populations - Lilu Ding; Ruoqi Dai; Dian Jin; Zhanyi Li; Jing Qian; Jiahao Zhu; Jingyou Miao; Hui Zhang; Jing Wang; Yan Xu; Yingjun Li (Archives of Public Health)
Abstract Background Osteoarthritis (OA), a leading cause of disability worldwide, is increasingly recognized for its systemic impact. Despite its prevalence, the age-dependent effects of OA remain underexplored, particularly regarding its association with comorbidities across the life course. Methods Using the UK Biobank (78,825 incident OA cases; 301,071 age-/sex-matched controls; age range: 40–86 years) and the CHARLS cohort (China, 5,735 participants, age range: 45–92 years), we employed Cox models with age as the time scale to estimate hazard ratios (HRs) for OA-associated comorbidities, including bone diseases, metabolic disorders, and mental health conditions, stratified by age at diagnosis. Analyses adjusted for sociodemographic factors and population-attributable fractions (PAFs) were calculated to quantify preventable burdens. Results OA was associated with significantly increased risks across multiple comorbidities. All comorbidities exhibited an age-dependent gradient: relative risks were highest in younger individuals and declined with age, while absolute risks increased due to OA’s higher prevalence in older populations. For example, HRs for metabolic disorders declined from 2.55 (95% CI: 2.36–2.76) in those aged 40–49 to 1.77 (95% CI: 1.74–1.81) in those aged ≥ 70. Validation in CHARLS confirmed these patterns. Conclusion The systemic effects of OA vary substantially by age at onset. Younger individuals face elevated proportional risks likely shaped by behavioral, occupational, and structural factors, while older adults bear a larger absolute burden. These findings underscore the need for age-sensitive strategies to reduce long-term health consequences of OA and promote healthy aging. Graphical Abstract